PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LAPA PADA PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA - Sujarwo, Rosalina Ariesta; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of current ratio, debt to equity ratio, return on asset, and total assetturnover to the profit changes on the automotive companies which are listed in Indonesia Stock Exchange in 2010-2013periods. The samples are the 12 companies which are engaged in the field of automotive in Indonesia Stock Exchange andthese automotive companies have been selected as samples by using saturated sampling. The analysis technique has been doneby using multiple regressions analysis. The result of the test shows that simultaneously current ratio, debt to equity ratio,return on asset, and total asset turnover have an influence to the profit changes. This condition indicates that the researchmodel is feasible to be continued for the next research. This result is supported by the acquisition of coefficient correlation is57.8% which shows that the correlation among the models which has been used in this research to the profit growth is quitefirm. The result of partial test shows that current ratio, debt to equity ratio, return on asset have significant influence to theprofit changes of the company. Meanwhile, the total asset turnover variable does not have any significant influence to theprofit changes.Keywords: Current Ratio, Debt to Equity Ratio, Return on Asset, Total Asset Turnover, and Profit Changes.